THE EFFECT OF CROSS FUNCTIONAL TRAINING AND THE WORK ENVIRONMENT TOWARDS WORK QUALITY IN THE MIDDLE OF THE COVID-19 PANDEMIC SITUATION (CASE STUDY: CJ LOGISTICS IN SEOUL, KOREA) - Ida Nyoman Basmantra; Aprilia Kusumaningtyas; Moch. Firmansyah (Jurnal Ilmiah Akuntansi & Bisnis, 2020)
The effect of Cross Functional Training and the Work Environment towards  Work Quality in the Middle of the Covid-19 Pandemic Situation. This study aims to determine the effect of cross functional training and work environment partially and simultaneously on work quality. The location of this research is, CJ Logistics. The population uses all employees, CJ Logistics and a sample of 30 respondents. The data analysis technique used validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, F test and t test. From the research results, the results obtained: (1) cross functional training has a significant positive effect on work quality, where the t value is 3.515 and a significance value is 0.002 <0.05. (2) the work environment has a significant positive effect on work quality, where the t-count value is 3.541 and a significance value is 0.002 <0.05. (3) Simultaneous cross functional training and work environment have a significant effect on work quality, where the significance value is 0.000 <0.05. The magnitude of the influence of the independent variables on work quality is 58.2%. Suggestions that can be given by researchers are that Cj Logistics is expected to routinely provide cross-functional training, make adequate air circulation, keep the workplace clean, provide a sense of security, and create task structures that are in accordance with employee abilities and build good cooperation patterns. Keywords: Cross functional training, work environment and work quality